Curcuma nakhonphanomensis (Zingiberaceae), a new species from the lower Mekong River basin, northeastern Thailand - PIYAPORN SAENSOUK; THAWATPHONG BOONMA; SURAPON SAENSOUK (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Saensouk P, Boonma T, Saensouk S. 2022. Curcuma nakhonphanomensis (Zingiberaceae), a new species from the lower Mekong River basin, northeastern Thailand. Biodiversitas 23: 6040-6048. Curcuma nakhonphanomensis Boonma, Saensouk & P. Saensouk sp. nov. (Zingiberaceae: Zingibereae) was distributed in Nakhon Phanom Province, northeastern Thailand. The morphological characteristic of this species makes it fall into Curcuma subgenus Ecomata, due to the presence of epigynous glands, lack of coma bracts and bracts fused only at the base, and production of open-form of flowers. This plant did not match any existing species after careful morphological examination and comparison of all allied species in the genus Curcuma, especially in subgenus Ecomata. Therefore, we described it here as a new species to science in the name of Curcuma nakhonphanomensis Boonma, Saensouk & P. Saensouk. The specific epithet is named according to the province's name of the type locality. The morphological characteristics description, illustrations, vernacular name, ecology, phenology, distribution, utilization, conservation status, and map of distribution are present. The comparison table of the new species and its allies species, including a revised key to 41 species of Curcuma subgenus Ecomata is provided.